World regional geography : a development approach - Johnson, Douglas L., 1943-; Haarmann, Viola, ....-; Johnson, Merrill L., ....-; Airriess, Christopher A., 1955- (Upper Saddle River (N.J.) : Pearson/Prentice Hall, 2010)
For introductory courses in World Regional Geography. Written by experts in their respective fields who are active in research, fieldwork, and teaching, this text teaches the character of the world's people, with a central theme of human development, for an issues-oriented overview of each region. An emphasis on subregions (places within regions) allows instructors to explore specific locales as they teach the themes of the course.
Includes bibliographical references and index.
Keywords: Developing countries -- Economic conditions; Aardrijkskunde -- Atlassen; Economic development; Economic geography; Economic history; Geografie -- Sociale geografie -- Algemene Werken